Konsep Kafa’ah Dalam Memilih Pasangan Hidup Menurut Empat Imam Madzhab - Moh. Miftahuzzaman; Suyud Arif; Sutisna Sutisna (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study examines the "Kafa'ah Concept In Selecting A Life Partner According To The Four Imams Of Madzhab". In more detail, discussing the process of determining a partner, it is recommended to choose one who is in agreement, balanced, level and equal. Although this is not a necessity, it is intended to produce harmony in order to avoid failure in fostering a household caused by striking differences, both differences in religion and in social strata. These differences can be a source of disputes which ultimately lead to family disharmony. This study aims to analyze how the views of four madhhab priests about the concept of kafa'ah in choosing a life partner. This research is a research that uses a normative approach with a qualitative descriptive method, namely describing the views of four priests of a school of thought. The research results obtained from the discussion of this research, namely that according to the scholars of the four schools of thought kafa'ah have different perceptions with the criteria of kafa'ah. Therefore, it is important to explain in this thesis the views of the four madzhab scholars regarding the standardization of kafa'ah in choosing a life partner. It was concluded that kafa'ah had an important role in marriage and the criteria differed among the four madzhab scholars, namely lineage, wealth, religious quality, employment, disability and independence. Keywords: Kafa'ah, Four of madzhab, Kafa'ah Criteria